Uses of cetyl cacaoateTM in lipstick development: sensory evaluation - Samuel Yap, Kian Chee; H. Sarini,; A. Aminah,; S. Sabariah, (Universiti Kebangsaan Malaysia, 2010)
The use of Cetyl CacaoateTM in lipstick formulation was evaluated by varying the porpotion of waxes mixture among carnauba wax, jojoba ester and Cetyl CacaoateTM based on Simplex centroid {3,3} experimental design. Sensory evaluation was carried out by nine trained panels using quantitative descriptive analysis (QDA) method. The attributes agreed in the sensory languages development session were easy to apply, off flavor, hardness, texture, moist, appearance on lip after use, glossy, oily, comfortability after use, and long lasting. Results showed that Cetyl CacaoateTM increased the score of easy to apply but decreased the score for hardness. Cetyl CacaoateTM in the lipstick formulation increased the oily feels whereas carnauba wax gave less oily effect. No off flavor was detected for all the samples. However, the panels had different perception on comfortability after use, and long lasting. The ratio of cosmetic waxes in lipstick formulation which gave scores close to reference sample were 1/2 Cetyl CacaoateTM : 1/2 jojoba ester and 2/3 Cetyl CacaoateTM : 1/6 jojoba ester : 1/6 lilin carnauba.